Entrepreneurial attitude of medical specialists at a hospital in Huancavelica, Peru - Lazo Vera, Jorge Omar (2020)
Objective: To measure the entrepreneurial attitude of medical specialists at a hospital in Huancavelica, Peru. To determine if age, sex, job tenure, type of contract, marital status, income and medical specialty influence their entrepreneurial attitude. Materials and methods: An observational, prospective and cross-sectional study. A Likert-scale questionnaire on entrepreneurial attitude was administered to 32 medical specialists. Also age, sex, job tenure, type of contract, marital status, income and medical specialty were assessed. Descriptive and inferential analyses were performed. Results: Eighty-five percent (85 %) of the study population showed a solid entrepreneurial attitude, while the remaining 15 % might be an entrepreneur. No participant rejected entrepreneurship as an option. Regarding the association between the entrepreneurial attitude and the studied factors, no significant differences were found in any variable. Conclusions: Eighty-five percent (85 %) of the study population showed a positive attitude towards entrepreneurship regardless of the studied associated factor.